Feasibility Study of Canine Epidermal Neural Crest Stem Cell Transplantation in the Spinal Cords of Dogs. (13th August 2015) - McMahill, Barbara G.; Spriet, Mathieu; Sisó, Sílvia; Manzer, Michael D.; Mitchell, Gaela; McGee, Jeannine; Garcia, Tanya C.; Borjesson, Dori L.; Sieber-Blum, Maya; Nolta, Jan A.; Sturges, Beverly K.
Abstract : This study tested the outcome of canine epidermal neural crest stem cell (cEPI-NCSC) grafts in the normal spinal cords of healthy bred-for-research dogs, developed novel protocols for ex vivo expansion and delivery of cEPI-NCSCs into the spinal cord, and labeled the cells for subsequent tracing of the graft by advanced imaging. The study demonstrated that cEPI-NCSC grafts survive in the spinal cords of healthy dogs with minimal functional adverse effects. Abstract: : This pilot feasibility study aimed to determine the outcome of canine epidermal neural crest stem cell (cEPI-NCSC) grafts in the normal spinal cords of healthy bred-for-research dogs. This included developing novel protocols for (a) the ex vivo expansion of cEPI-NCSCs, (b) the delivery of cEPI-NCSCs into the spinal cord, and (c) the labeling of the cells and subsequent tracing of the graft in the live animal by magnetic resonance imaging. A total of four million cEPI-NCSCs were injected into the spinal cord divided in two locations. Differences in locomotion at baseline and post-treatment were evaluated by gait analysis and compared with neurological outcome and behavioral exams. Histopathological analyses of the spinal cords and cEPI-NCSC grafts were performed at 3 weeks post-transplantation. Neurological and gait parameters were minimally affected by the stem cell injection. cEPI-NCSCs survived in the canine spinal cord for the entire period of investigation and did not migrate or proliferate. Subsets of cEPI-NCSCs expressed the neural crest stem cell marker Sox10. There was no detectable expression of markers for glial cells or neurons. The tissue reaction to the cell graft was predominantly vascular in addition to a degree of reactive astrogliosis and microglial activation. In the present study, we demonstrated that cEPI-NCSC grafts survive in the spinal cords of healthy dogs without major adverse effects. They persist locally in the normal spinal cord, may promote angiogenesis and tissue remodeling, and elicit a tissue response that may be beneficial in patients with spinal cord injury. Significance: It has been established that mouse and human epidermal neural crest stem cells are somatic multipotent stem cells with proved innovative potential in a mouse model of spinal cord injury (SCI) offering promise of a valid treatment for SCI. Traumatic SCI is a common neurological problem in dogs with marked similarities, clinically and pathologically, to the syndrome in people. For this reason, dogs provide a readily accessible, clinically realistic, spontaneous model for evaluation of epidermal neural crest stem cells therapeutic intervention. The results of this study are expected to give the baseline data for a future clinical trial in dogs with traumatic SCI.